Key performance indicators in occupational health and safety of hospitals: A scoping review with meta-analysis - Georgios I. FARANTOS; Georgios DOUNIAS (GIornale Italiano di Psicologia e Medicina del Lavoro)
Introduction: This study aimed to synthesize and map what was reported in the international literature on the relationship between Key Performance Indicators (KPIs) and hospital Occupational Health and Safety (OHS). Methods: For this scoping review, PubMed, Medline, and Scopus were searched. We did separate random-effects meta-analyses for institutional outcomes using the KNIME software. Results: Of the identified 6,698 records, 10 were eligible, and data were available for 10, all with a low to moderate risk of overall bias. A particularly low correlation between Protective and Preventive Services (PPS) and KPI studies in hospital OHS was demonstrated. For the correlation KPI score – Occupational Physician (OP) score, KPI score – Risk Assessment (RA) score, and OP score – RA score, the values are 0.999, 0.595, and 0.408, while the p-values are 0.0185, 0.778, and 0.893, respectively. Data analysis found that studies of KPIs in OHS in hospitals did not sufficiently consider the institutional representations of PPS, safety technician (ST), OP, Occupational Health and Safety Management Systems (OHSMS), and RA and how they interact with the planning and implementation processes of the KPIs. Discussion and Conclusions: This study found through data analysis that studies of KPIs in OHS in hospitals did not adequately consider PPS, ST, OP, OHSMS, and RA and how these elements interact with planning and implementing these KPIs. The contribution to knowledge in this research filled this gap identified in the literature.